Sokolarjenje z vidika trajnostne rabe narave - Čas, Miran (Gozdarski vestnik, 2008)
The article presents the study of influence of falconry on the sustainable useof nature and conservation of biodiversity. The study comprised 15 falconrybirds of 6 diverse species. This article presents the results of smallgame hunting in the Special Intent Hunting Ground "Fazan" (the pheasant) Beltinci and grey crow hunting on the Jože Pučnik Airport in Ljubljana.
Keywords: sokolarstvo; bird; ptice; ujede; lov; sustainable development; trajnostni razvoj